TRADISI MELAHIRKAN SUKU NAULU DI POSUNE KABUPATEN MALUKU TENGAH - Norce Kainama; Denicell Paulina Tetelepta; Femi Serly Tuhumena (Jurnal Keperawatan Indonesia Timur (East Indonesian Nursing Journal), 2021)
Background: Maternal mortality rate in Central Moluccas District registerd 4 casses in 2012, 10 casses in 2013. Since a long time ago woman protection has caried out by Naulu Tribal who life at beach of Region South Seram by isolatinive birthg woman who will give birth to a small house with a size 2x2 meter from settlements (15–20 meter). Objective: The aims of this research is how the protection measures by exile women giving birth by the Naulu Tribe towards the welfare of mothers and babies. Methodes: Qualitative ethnographic design. The main participants for mothers who will give birth at Posune and triangulation participants are traditional healers, husbands, families, traditional leaders, community leaders and midwives. Data were collected through in-depth interviews and observation. measurement using content analysis. Result: delivery in Posune a must for each woman in Naulu Tribal. All need of woman suplay by birth traditional attendant and others woman, depend on any family, ecample family S consume some herbalis made by birth traditional attendan. The infant consume breast feeding, caring from birth traditional attendant with control by midwifry. Comfort and enviroment temperature from traditional stove, no infection sign for umbilical. Conclusion: Traditional leader control for the tradition, community leader control repect at tradition. Midwifery good accept from the tribal and olways work with birth tradional attendant.